2016
DOI: 10.1093/nar/gkw984
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic spike-in standards for high-throughput 16S rRNA gene amplicon sequencing

Abstract: High-throughput sequencing of 16S rRNA gene amplicons (16S-seq) has become a widely deployed method for profiling complex microbial communities but technical pitfalls related to data reliability and quantification remain to be fully addressed. In this work, we have developed and implemented a set of synthetic 16S rRNA genes to serve as universal spike-in standards for 16S-seq experiments. The spike-ins represent full-length 16S rRNA genes containing artificial variable regions with negligible identity to known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
175
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(179 citation statements)
references
References 47 publications
4
175
0
Order By: Relevance
“…Many recent publications have highlighted the use of the spike-in for 16S-rRNA encoding gene surveys, both for QC as well as a normalization tool to move from relative towards absolute abundance [13,22,23]. We built upon these studies to demonstrate the use of a spike-in for validating a shotgun/untargeted metagenomics workflow.…”
Section: Resultsmentioning
confidence: 99%
“…Many recent publications have highlighted the use of the spike-in for 16S-rRNA encoding gene surveys, both for QC as well as a normalization tool to move from relative towards absolute abundance [13,22,23]. We built upon these studies to demonstrate the use of a spike-in for validating a shotgun/untargeted metagenomics workflow.…”
Section: Resultsmentioning
confidence: 99%
“…These pathogens are the focus of pathogen surveys across the United States, as management of Phytophthora ‐infected zones seasonally impacts timber harvesting, recreation, and restoration activities (U.S. Department of the Interior, Bureau of Land Management, and U.S. Department of Agriculture, Forest Service ). Given their ubiquity, Phytophthora , Saprolegnia , or similarly cosmopolitan oomycetes may also provide “internal positive” controls that can be used in lieu of spike‐in controls (Tourlousse et al, ) for sample validation, or as a check for errors in collection (e.g., filtration) or DNA extraction methods. Our assay included primers for additional animal pathogens, specifically amphibian chytrid fungus ( Batrachochytrium dendrobatidis Longcore, Pessier & Nichols; Olson et al, ) and the fungus that causes white‐nose syndrome in bats ( Pseudogymnoascus destructans (Blehert & Gargas) Minnis & Lindner; Blehert et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…de Bary), and other trees and shrubs (Hansen et al, 2012). Saprolegnia, or similarly cosmopolitan oomycetes may also provide "internal positive" controls that can be used in lieu of spike-in controls (Tourlousse et al, 2017) for sample validation, or as a check for errors in collection (e.g., filtration) or DNA extraction methods.…”
Section: Microfluidic Metabarcoding Extends Opportunities To Examinmentioning
confidence: 99%
“…Second, the HFD‐induced changes in microbiota are often inconsistent, likely due to differences in the experimental approaches. This can be different, for example, depending on (i) whether the microbiota was analysed in the faeces or in the intestinal contents such as the caecum; (ii) different methodologies used for sample processing such as DNA extraction or sequencing ; (iii) the duration of the intervention with a HFD ; (iv) the source of dietary fat ; (v) the concentration of sucrose in the diet and (vi) the initial microbiota composition and the genetic background of the animals . Additionally, a recent study found that mice from the same strain, which consumed the same diet, but reside in different facilities within Germany, had significantly different faecal microbiota .…”
Section: Intestinal Microbiota Composition Associated With Diet‐inducmentioning
confidence: 99%